2020
DOI: 10.1021/acs.jnatprod.0c00699
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Semisynthetic Chalcones as Dual FLT3 and Microtubule Polymerization Inhibitors

Abstract: Activating mutations in FLT3 receptor tyrosine kinase are found in a third of acute myeloid leukemia (AML) patients and are associated with disease relapse and a poor prognosis. The majority of these mutations are internal tandem duplications (ITDs) in the juxtamembrane domain of FLT3, which have been validated as a therapeutic target. The clinical success of selective inhibitors targeting oncogenic FLT3, however, has been limited due to the acquisition of drug resistance. Herein the identification of a dual F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Malik et al 163 identified a dual tubulin−FMS-like tyrosine kinase 3 (FLT3) chalcone 73 (Figure 17C). It reduced phosphorylation of two key downstream targets of FLT3, namely, signal transducer and activator of transcription 5 (Stat5) and/or extracellular signal-regulated kinase (ERK), which is consistent with the antiproliferative activity toward FLT3-internal tandem duplications (ITDs) mutation cell lines MV-4−11 (IC 50 = 0.24 μM) and MOLM-13 (IC 50 = 0.20 μM).…”
Section: Dual Inhibitors Of Tubulin and Othermentioning
confidence: 99%
“…Malik et al 163 identified a dual tubulin−FMS-like tyrosine kinase 3 (FLT3) chalcone 73 (Figure 17C). It reduced phosphorylation of two key downstream targets of FLT3, namely, signal transducer and activator of transcription 5 (Stat5) and/or extracellular signal-regulated kinase (ERK), which is consistent with the antiproliferative activity toward FLT3-internal tandem duplications (ITDs) mutation cell lines MV-4−11 (IC 50 = 0.24 μM) and MOLM-13 (IC 50 = 0.20 μM).…”
Section: Dual Inhibitors Of Tubulin and Othermentioning
confidence: 99%
“…The compound forms two hydrogen bonds with tubulin on Leu255 and Cys241 residues. The phenyl residue adjacent to the carbonyl group forms Π-σ interactions with Leu248, and the other aromatic residue interacts with residues Ala180 and Lys254 [ 224 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Please see ref for instrumentation. Naphthazarin ( 1 ); isoplumbagin ( 2 ); , 3-chlorojuglone ( 3 ); , juglone ( 4 ); , 2-bromo-3-methyl-1,4-naphtho-quinone ( 5 ); 6-methoxynaphthoquinone ( 6 ); , 2-butenoic acid, 4-[1,4-dihydro-3-[4-(2-methyl-1,3-dioxolan-2-yl)-3-oxobutyl]-1,4-dioxo-2-naphthalenyl]-3-methoxy-, methyl ester ( 8 ); 2-(2-buten-1-yl)-3-hydroxy-1,4-naphthoquinone ( 9 ); β-lapachone ( 10 ); , and 2-(chloromethyl)­quinizarin ( 11 ) were prepared and characterized following procedures reported in the literature.…”
Section: Experimental Sectionmentioning
confidence: 99%